Capturing Time-of-Flight data with confidence - Reynolds, Malcolm; Doboš, Jozef; Peel, Leto; Weyrich, Tim; Brostow, Gabriel J. (Proceedings of the IEEE Computer Society Conference on Computer Vision and Pattern Recognition, 2011)
Time-of-Flight cameras provide high-frame-rate depth measurements within a limited range of distances. These readings can be extremely noisy and display unique errors, for instance, where scenes contain depth discontinuities or materials with low infrared reflectivity. Previous works have treated the amplitude of each Time-of-Flight sample as a measure of confidence. In this paper, we demonstrate the shortcomings of this common lone heuristic, and propose an improved per-pixel confidence measure using a Random Forest regressor trained with real-world data. Using an industrial laser scanner for ground truth acquisition, we evaluate our technique on data from two different Time-of-Flight cameras 1 . We argue that an improved confidence measure leads to superior reconstructions in subsequent steps of traditional scan processing pipelines. At the same time, data with confidence reduces the need for point cloud smoothing and median filtering. © 2011 IEEE.
CRIS-Team Scopus Importer:2022-07-26